2011
DOI: 10.1542/neo.12-3-e130
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Nutrition in the Neonatal Intensive Care Unit

Abstract: Neonatal parenteral nutrition (PN) is readily available in many hospitals and plays an essential role in the management of sick and growing preterm and term infants. PN can be used as the sole source of nutrition support for infants who cannot be fed or as an adjunct to enteral feeding. Preterm infants are a particularly vulnerable population because they are born at a time, if they had remained in utero, of rapid intrauterine brain and body growth. The impact of early malnutrition can have long-lasting negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 45 publications
0
33
0
13
Order By: Relevance
“…The success in pediatric surgery is related to the preoperative and postoperative intensive care in addition to the right surgical indication and techniques. 4,6 CONCLUSION It was observed that BMI values were under the standards of WHO in NBs fed TPN and followed until the first age in our study. We think that monitoring of growth hand development values of the greater number of babies fed TPN was rather beneficial to catch the standards during childhood.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The success in pediatric surgery is related to the preoperative and postoperative intensive care in addition to the right surgical indication and techniques. 4,6 CONCLUSION It was observed that BMI values were under the standards of WHO in NBs fed TPN and followed until the first age in our study. We think that monitoring of growth hand development values of the greater number of babies fed TPN was rather beneficial to catch the standards during childhood.…”
Section: Discussionmentioning
confidence: 47%
“…6,9 The aim of studying of the growth and development in children is to protect the rights of children ensuring their physical, mental social and emotional developments. 2 The early use of aminoacids accelerates the growth and it affects the neuro-growth outcomes positively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Todas las unidades inician la glucosa en NP a las dosis recomendadas en función de la madurez del recién nacido 5,15 , tal como en otros países 5 . En el pretérmino, la mayoría adopta la dosis máxima de 13 mg/kg/min, considerado como límite de oxidación de la glucosa 5,6 .…”
Section: Discussionunclassified
“…Данная «агрессивная» тактика с применением высоких доз белка имитирует объем поступления питательных веществ как при внутриутробном развитии плода соответствующего периода гестации, существенно снижая риск нарушений физического и нервно-психического развития в дальней-шем. «Агрессивная» тактика питания хорошо переносится детьми с ОНМТ и ЭНМТ и обеспечивает адекватные тем-пы физического развития в постнатальном периоде без неблагоприятных исходов [47].…”
Section: обзор литературыunclassified